Analisis Penggunaan Kata Slang dalam Video Wawancara Rich Chigga dengan Joey Franchize - Lay Bole, Godlief Anjas; I Gde Agoes Caskara Surya Putra (English Education Department, 2023)
The phenomenon of slang words is one of the factors of English literature development in modern era. Slang word is an identity of individual’s linguistic style to express their norms in the society, by conveying certain types of slang and placing it within different contextual topic of discussion. In the context of slang word distribution and role in daily conversation Slang language used under certain circumstances whether it’s informal or formal and to whom they speak to and also considered the politeness to the elder people. To study further of slang usage among people in context of media, this research used the video interview of Rich Chigga with Joey Franchize as an object of examination. The research employs qualitative approach, Qualitative research is used through observation of the video and aimed to extract information about slang words conveyed by both communicators and classified it according to Allan and Burdige of The Types of Slang Theory. The classifications are divided into four parts, namely Fresh and Creative, Imitative, Clipping, Flippant, and Acronym. The classifications of data are studied further by using American Slang Theory according to Zhou & Fan to analyze further the meaning of exemplary data based on Pursuit or Self-Identity, Emotive Feelings, and Achieving Politeness. The result showed 22 data collected from the video and the most slang type expressed is Imitative due to its connection with urban world and modern culture embodied by the communicators.